Disain dan Implementasi Atenna BOW TIE Pada Frekuensi 750 MHz Untuk Aplikasi Penerima TV - waluyo; Muhammad Syirajuddin; Moh Abdullah Anshori (Politeknik Negeri Malang, 2020)
Many types of antennas work on the UHF band, including a 1 / 2l dipole antenna, Yagi-Uda array antenna, log periodic antenna, etc. The antenna of this type, its physical dimensions are adjusted according to the wavelength. The higher the working frequency, the shorter the wavelength, so the shorter the antenna's physical length. Bow tie antennas are often used as a TV receiver antenna, besides being relatively easy to manufacture, simple and significant. In this study, the antenna designed is a bow-tie antenna (butterfly) which works at a UHF frequency of 750 Mhz, arranged in an array, then fed with a 4: 1 balun (antenna impedance 300 ? to 75 ?), using a toroidal balun. With an air core in order to match the coaxial cable impedance of 75 ?. Antenna material from aluminum (solid). The research site was carried out in the Polinema Telecommunication laboratory. Antenna test results at an operating frequency of 750 Mhz show that the value of RL (return loss): - 11 dB, the coefficient of reflection G= 0.282, and the VSWR magnitude value = 1.786. The highest gain measurement occurs at the frequency: 567.25 Mhz (channel 33), which is 10.45 dB, and the average gain of the antenna is 3.19 dB. Because the VSWR price is less than 2, it can be said that the bow-tie antenna is still quite decent or good. It meets the criteria of an antenna parameter